Pilot Study on Blast Movement Monitoring at Geita Gold Mine - F Mwijage (The Australasian Institute of Mining and Metallurgy, 2012)
"The benefits of measuring blast movement to reduce ore loss and dilution have been recognised by many people for many years and various methods have been used with limited success. Geita Gold Mine is running the pilot study on the blast movement monitoring (BMM) system which is a revolutionary method developed and patented by the University of Queensland and Blast Movement Technology (BMT). The system consists of directional transmitters placed within the shot prior to blasting, which are then located after the blast with a special detector and then the data is processed with purpose-designed software.As part of continuous improvement on grade control, Geita Gold Mine is running a research project in all operating pits with the objective of: quantifying the three-dimensional blast muck pile movement and finally utilise the movement data to define post-blast ore polygons and incorporate the movement dynamics during block modelling,quantify the potential savings for ore loss and dilution,improve mine geologists knowledge of blast dynamics, andstimulate greater co-operation between drill and blast engineers and geologists to achieve optimum blast designs.To any operation with selective mining, it is critical to the economics of an operation to control ore loss and dilution; getting it wrong will result in significant lost revenue. Implementation of ongoing pilot study on electronic balls as determinant on blast movement dynamics on ore would be of longer term solution and big investment pay back.CITATION:Mwijage, F, 2012. Pilot study on blast movement monitoring at Geita gold mine, in Proceedings Narrow Vein Mining 2012 , pp 49-58 (The Australasian Institute of Mining and Metallurgy: Melbourne)."